2004
DOI: 10.3354/meps276209
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic differences in claw size and performance in an introduced crab predator Carcinus maenas

Abstract: Introduced predators must forage effectively to persist in new areas, and effective resource use is correlated with a predator's trophic (feeding) structures. The extent to which trophic morphology responds to spatial variation in prey resistance, and the time scale of that response, however, are not well understood. The introduced European green crab Carcinus maenas, which has expanded its range in the northwest Atlantic Ocean over the last century and encountered a latitudinal cline in prey armor, offers an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 82 publications
0
53
1
Order By: Relevance
“…And for density-mediated cascades, it is reasonable that the top predator's evolutionary history with common prey (and its own predators) selected a dietary preference, hunting mode, and/or morphological features that facilitate hunting and eYciently consuming a widely available intermediate consumer (Vermeij 1982b). Although the behavior underlying trophic cascades could be learned by individual top predators and intermediate consumers, each animal's capacity for learning would be inXuenced by the presence/absence of innate morphological or behavioral traits that would increase Wtness and ultimately be selected for within a population over time (Berger et al 2001;Cox and Lima 2006;Smith 2004). We therefore suspect that a common feature of functioning cascades is that the top predator and intermediate consumer species share an evolutionary history and/or have historical exposure with similar types of predator and prey species so that their predator and anti-predator strategies are well matched.…”
Section: Discussionmentioning
confidence: 99%
“…And for density-mediated cascades, it is reasonable that the top predator's evolutionary history with common prey (and its own predators) selected a dietary preference, hunting mode, and/or morphological features that facilitate hunting and eYciently consuming a widely available intermediate consumer (Vermeij 1982b). Although the behavior underlying trophic cascades could be learned by individual top predators and intermediate consumers, each animal's capacity for learning would be inXuenced by the presence/absence of innate morphological or behavioral traits that would increase Wtness and ultimately be selected for within a population over time (Berger et al 2001;Cox and Lima 2006;Smith 2004). We therefore suspect that a common feature of functioning cascades is that the top predator and intermediate consumer species share an evolutionary history and/or have historical exposure with similar types of predator and prey species so that their predator and anti-predator strategies are well matched.…”
Section: Discussionmentioning
confidence: 99%
“…Juanes & Hartwick 1990, Behrens Yamada & Boulding 1998. Second, the use-induced changes generated in our experiment were comparable in magnitude to differences in relative crusher claw height (approximately 9%) between southern and northern populations of Carcinus maenas in the Gulf of Maine (Smith 2004), and these geographic differences affect foraging performance. By offering crabs Littorina obtusata of increasing size, Smith (2004) demonstrated that the larger-clawed southern crabs crushed both thick-and thin-shelled snails up to a greater size than did the smaller-clawed northern crabs of similar carapace width (see also Rochette et al 2007).…”
Section: Discussionmentioning
confidence: 85%
“…thicker shelled, more resistant snails are found in the south rather than in the north (Trussell 2000). In contrast, cutter claws showed no geographic differences in relative size (Smith 2004). The correlation between crusher claw size and prey armor suggests an adaptive trophic response by the predator to its prey, but the causal mechanism (diet-induced plasticity, rapid selection on claw size) has not been established.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations